54 Eastern Red Cedar Targeted Grazing with Goats: Tree Height Significance. (12th April 2022) - Hartsfield, Alanna; Smart, Alexander; Xu, Lan; Froehlich, Kelly
Abstract: Eastern red cedar (ERC; Juniperus Virginiana L .) encroachment into grassland ecosystems, facilitated by fire suppression and overgrazing, threatens the long-term health of the Northern Great Plains. Goats consume juniper through defoliation and debarking, and debarking causes branch death. ERC do not resprout, meaning trunk girdling can effectively kill the tree, making targeted grazing with goats a potential control tool, though little is known about targeted grazing with goats on ERC. The objective of this project is to investigate how goats defoliate and debark ERC of different heights. Moderately stocked (95 AUD∙ha -1 ) Spanish cross-bred goats grazed 24-hour periods in each of 4 replicate ERC-invaded 0.056 ha paddocks (average 117 trees∙paddock -1 ). ERC of 5 height classes, up to 250 cm at 50 cm increments, were permanently tagged in each paddock. Defoliation was measured by volume (⅓πr 2 h) reduction (%) from pre- to post-treatment, branch browse was measured as branches browsed (%) below the browse line, and debarking was measured by trunk debarked (%) below the browse line. Tree height was a significant predictor of defoliation (r 2 = 0.63, n = 159, P < 0.001) and debarking (r 2 = 0.53, n = 159, P < 0.001). ERC < 100 cm tall were significantly more defoliated ( P < 0.05, x̄ = 74%) and ERC 50-100 cm had significantly more branches browsed up to the browse line ( P < 0.05, x̄ = 85%), while ERC > 100 cm were significantly more likely to be debarked ( P < 0.05, x̄ = 45%). Average browse line for trees 100-250 cm was 186 cm. Our results suggest that goats disproportionally defoliate and debark short (1-100 cm) and tall (100-250 cm) ERC trees, respectively. Moderately stocked targeted grazing with goats could be an effective ERC site pre-treatment for prescribed fire or other control methods.